Desconexão longitudinal de habitats em riachos neotropicais: ictiocenose sob influência de tubulações - Mariano, José Roberto (2011)
The insertion of culverts in streams may cause habitat degradation, changing patterns of migration and dispersal of species, causing deterioration of biological diversity over time, favoring the disconnection of the habitat. This study aimed to evaluate the fish assemblages between the upstream and downstream segments of box and circular culverts in neotropical streams. Specifically we intend to analyze the composition and structure of the ichthyofauna and its possible spatial patterns, as well as the occurrence of spawning. Sampling for fish fauna were carried out monthly between November 2009 and October 2010, with various fishing gear such as gillnet, sieve, rod and castnet. Samples of ichthyoplankton were conducted between October 2009 and March 2010, with plankton net. During the period 2220 individuals were collected, with 901 fish in segments of circular culvert and 1,310 fish in segments of box culvert, belonging to 33 species. Catches were similar in both upstream and downstream segments of the circular culvert, whereas in the box culvert the fish abundance was just over in the upstream segment against downstream. The Characiformes dominated with a larger number of individuals in the upstream stretch of both culverts. On the other hand, the Siluriformes were abundant in the downstream stretch of the circular culvert, with similar abundances among the sections of box culvert. The richness and diversity of species differed among the sections of circular culvert (higher value in downstream), while values were similar to portions of the box culvert. The most abundant species were Astyanax altiparanae, A. paranae, A. fasciatus, Ancistrus sp., and Hypostomus sp., but with differences in the occurrence of the latter two species: these were more abundant in downstream segment of the circular culvert, and similar in sections of box culvert. The ichthyoplankton sampled was very low, with records of 36 eggs, 05 juveniles and 03 larvae, especially in the downstream section of the culverts. The ichthyofauna obtained distinct patterns among the culverts and in particular between the upstream and downstream sections of circular culvert. The data presented here showed that the circular culvert seems to provoke more limitation to fish movement, acting as a barrier to the species, especially for the Siluriformes, which reflects the variations that exist in abundance, richness and diversity of species. This indicates the need for further studies in neotropical streams intercepted by culverts, aimed to assemblies of fish and their movement. Such studies may subsidize the responsible sectors for the implementation of these structures to propose possible solutions to improve the habitat conditions, adapting the engineering biology of the species.